Usefulness of Endoscope-Assisted Microsurgery for Removal of Vestibular Schwannomas - Kumon, Yoshiaki; Kohno, Shohei; Ohue, Shirou; Watanabe, Hideaki; Inoue, Akihiro; Iwata, Shinji; Ohnishi, Takanori (Journal of Neurological Surgery Part B: Skull Base, 2012)
The usefulness of endoscope-assisted microsurgical removal of vestibular schwannomas in the internal auditory canal (IAC) was evaluated. Microsurgical removal using the endoscope was done in 28 procedures and microsurgical removal without an endoscope was done in 43 procedures. A retrosigmoid approach was used. The tumor location in the IAC was classified as grade 1 (located up to the mid-portion), 2, 3, or 4 (located up to the fundus with bony destruction) according to the tumor extent, and residual tumor in the IAC was evaluated as grade A (remnant tumor was not observed), B, C, or D (remnant tumor was observed over the mid-portion) according to the extent of remnant tumor. The residual tumor in the IAC was less in the endoscope-assisted group than in the microsurgery group. There was a significant difference only in grade 2, that is, tumor located beyond the mid-portion of the IAC. There was no significant difference in the results of preservation of useful hearing, facial nerve function, and tumor recurrence between the two groups. The benefit of endoscope-assistance microsurgery was shown for those patients whose tumors extended beyond the mid-portion of the IAC but did not reach the fundus.
Keywords: vestibular schwannoma; endoscopy; retrosigmoid approach; internal auditory canal